2022
DOI: 10.1177/17588359221130503
|View full text |Cite
|
Sign up to set email alerts
|

Histologic transformation in lung cancer: when one door shuts, another opens

Abstract: Histologic transformation (HT) is a major cause of drug resistance to therapy in patients with lung cancer. HTs to small-cell lung cancer (SCLC) have been reported frequently in patients with epidermal growth factor receptor ( EGFR)-mutated lung cancer. Although HTs have an impact on the clinical outcomes in patients owing to a high refractoriness to treatments, there is limited data on the prevalence, causes, mechanisms, treatment efficacy, and future treatment strategies. In this review, we assess the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…Our results showed that patients who received rst-line treatment with atezolizumab or durvalumab in combination with chemotherapy experienced no signi cant difference in OS. The chemotherapy regimen of cisplatin combined with etoposide is the standard rst-line treatment for extensive-stage SCLC [20]. The results of our study indicated that using atezolizumab or durvalumab combined with standard chemotherapy regimens as rst-line therapy in extensive-stage SCLC is effective and feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 66%
“…Our results showed that patients who received rst-line treatment with atezolizumab or durvalumab in combination with chemotherapy experienced no signi cant difference in OS. The chemotherapy regimen of cisplatin combined with etoposide is the standard rst-line treatment for extensive-stage SCLC [20]. The results of our study indicated that using atezolizumab or durvalumab combined with standard chemotherapy regimens as rst-line therapy in extensive-stage SCLC is effective and feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 66%
“…For the 3 patients who underwent liquid biopsies only in this study, all of them were controlled by subsequent osimertinib treatments. Small cell transformation has also been reported as a resistance mechanism to prior osimertinib therapy in a previous study ( 44 ). According to the clinical treatment response to osimertinib in the 3 patients who underwent liquid biopsies only, the possibility of small cell transformation was very low, and the 3 patients were still included in this study.…”
Section: Discussionmentioning
confidence: 68%
“…Small cell lung cancer transformation is a rare (<5%) acquired resistance to previous EGFR-TKI treatment ( 44 ). In this study, 2 patients had small cell transformation according to tissue rebiopsy and were excluded from further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the resection criteria are controversial among locally advanced lung cancer in the era of immunotherapy, the optimal assessment criteria for operability following conversion therapy are also transformation is a major mechanism of drug resistance in lung cancer patients. Small-cell lung cancer (SCLC) transformation has been reported frequently in NSCLC patients after targeted therapy (33). However, histologic transformation between adenocarcinoma and squamous cell carcinoma after ICIs treatment is unusual.…”
Section: Discussionmentioning
confidence: 99%